Morphometrical Study of human neonatal cerebral cortex (Age of 28 day): Bader, K. Hameed1; Ayad, H. Ibraheem1 and Sammira, A-H. Abdullah2 - Hameed, Bader K. (The Iraqi Journal of Veterinary Medicine, 2017)
The character and timing of gyral and sulci development is one manifestation of the complex orchestration of human brain development. This work describes the morphometry and thickness measurement of human neonate cerebral cortex at age of 28 days. Four Brains samples were fixed in 10% neutral buffer formalin for 24 hrs. Slides from various brain regions were prepared and routine hamatoxylin and eosine staining procedure was applied using histological technique. The present results clarify that the brain mean measurement from the frontal to the occipital pole was 189.6 mm, while the measurements of the frontal, parietal, temporal and occipital cortices were 4.06, 3.84, 3.48 and 3.68 mm, respectively.